POTENSI TRADISI MEGIBUNG DI KABUPATEN KARANGASEM, BALI SEBAGAI DAYA TARIK WISATA BUDAYA - Wiratnaya, I Nyoman (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2010)
Megibung, a traditional manner of eating in Bali, can contribute to enrich culture tourism activities. The research analysis the potentials of this cultural activities as a tourist interest and activities. Using a qualitative research design, a number of key informants were interviewed about the activity and the possibilities to use it as one of the cultural tourism activities. Interviews were also conducted to some hotel and travel operators who have promoted the activity to their guests. It is found out that 'megibung' is potential to be developed as a culture tourism attraction or activity.